(untitled) (Latakia University Journal -Biological Sciences Series, 2019)
تهدف هذه الدراسة إلى معرفة نوعية الدبال المتكون في ترب ذات مادة أصل مختلفة، وتحت تأثير غطاء نباتي متنوع . أوضحت الدراسة لتسعة قطاعات أرضية مختلفة ومنتشرة في منطقة الدراسة تفوق الأحماض الهيومية مقارنة بالأحماض الفولفية تحت تأثير الغابات عريضة الأوراق، وبالمقابل كانت الأحماض الفولفية سائدة عند مقارنتها بالأحماض الهيومية تحت تأثير الغابات الصنوبرية ، كما لوحظ زيادة الهيومين والمجموعات الوظيفية للأحماض الدبالية المرتبطة بالكالسيوم والطين مع انخفاض المجموعات الوظيفية الحرة ، وكان متوسط عمق الأفق A (20 سم)، بينما تراوحت كمية المادة العضوية ما بين (2.83 – 9.30 %) في الأفق A ، وبلغت نسبة الأحماض الهيومية إلى الأحماض الفولفية ما يعادل الواحد. ويلاحظ وجود علاقة ارتباط بين المجموعات الوظيفية المرتبطة بالكالسيوم والطين وكذلك توجد علاقة ارتباط إيجابية بين محتويات الطين والمجموعة الوظيفية المرتبطة به، أيضاً بين الهيومين ومحتوى الطين. كما إن وجود آفاق تحت سطحية فاتحة اللون بشكل واضح تحت الغابات الصنوبرية وخاصة في منطقة بلوران-محافظة اللاذقية لا يمكن أن يعزى إلى الفعل التخريبي للأحماض الفولفية، وما يدل على ذلك عدم ملاحظة انخفاض كبير في محتوى الطين في الأفق تحت السطحي. The objective of this study was to determine the humus quality, which were formed in soils of different parent materials and under different natural vegetation cover. The study of nine soil profiles under Deciduous trees forest showed an increase of humic acid contents in comparison with fulvic acids, whereas in soils under pine forests, we found that fulvic acids were dominant comparing with humic acids. We also observed an increase in humine and humic acids functional groups that are fixed by calcium and clay. In addition a decrease in free functional groups was observed. The average horizon “A” depth was about 20 cm. The humus contents of horizon “A” varied between 2.83 and 9.30 % and the ratio of humic to fulvic acids was about 1. A positive correlation was observed between the functional group which was fixed by calcium and that which was fixed by clay. We also observed a positive correlation between the clay contents & the functional clay-fixed group, and also between the humine and the clay contents. The presence of the clear colored sub surface horizon under the pine forests, especially in Balloran region in Lattakia, could not due to the defective effect fulvic acids, this is evident by the absence of de crease in clay content in the sub surface horizon.